A FRAMEWORK FOR DEVELOPING SMART SOCIAL MEDIA PLATFORMS (FUDMA JOURNAL OF SCIENCES, 2025)
Social media networks have revolutionized the activities of this age. Larger populations are using social media for education, exchange of ideas, business, marketing, fun, games, commerce and so on. However, there exists a fundamental challenge in this media, which is, the identity insincerity and theft. Users of social media create so many accounts for themselves and use these accounts for frauds. Some use other people information like names, pictures and profile to create multiple accounts for their dubious benefits. This has posed many fears on user not to believe in most media engagements. Connecting and communicating to some people in other locations of the world comes with a lot of doubt, fears and difficulties in exchanging business and expertise ideas which is one of the hallmarks of the social media. In dealing with these challenges, this paper has presented a framework for deploying smart social media platforms for enhanced information security and eliminating multiple opening/using of social media platform by same individual for fraudulent activities. This framework was developed using Object Oriented Methodology and C# was used to implement the prototype platform. Visual Studio was used as the IDE for the developed platform. The platform output shows its viability in preventing multiple account creation by users. The platform performance is shown in the implementation output of the system whereby the system will prevent the creating of multiple accounts and the use of other people information in creating a new account.
Keywords: Framework; Information Security; Social Media; Platform; Software